2019
DOI: 10.48550/arxiv.1901.08082
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Cooperative Online Learning: Keeping your Neighbors Updated

Nicolò Cesa-Bianchi,
Tommaso R. Cesari,
Claire Monteleoni

Abstract: We study an asynchronous online learning setting with a network of agents. At each time step, some of the agents are activated, requested to make a prediction, and pay the corresponding loss. The loss function is then revealed to these agents and also to their neighbors in the network. Our results characterize how much knowing the network structure affects the regret as a function of the model of agent activations. When activations are stochastic, the optimal regret (up to constant factors) is shown to be of o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 6 publications
1
3
0
Order By: Relevance
“…Both these regret bounds match the rates mentioned for the context-free case in (Cesa-Bianchi et al, 2019b;Bar-On & Mansour, 2019). Moreover, when γ = 1, then the bound on the group regret matches the lower bound shown in the nonstochastic case (Cesa-Bianchi et al, 2019a).…”
Section: Extensionssupporting
confidence: 81%
See 1 more Smart Citation
“…Both these regret bounds match the rates mentioned for the context-free case in (Cesa-Bianchi et al, 2019b;Bar-On & Mansour, 2019). Moreover, when γ = 1, then the bound on the group regret matches the lower bound shown in the nonstochastic case (Cesa-Bianchi et al, 2019a).…”
Section: Extensionssupporting
confidence: 81%
“…In this paper, we use the LOCAL communication protocol (Suomela, 2013;Fraigniaud, 2016;Linial, 1992), which has recently seen an increase in interest in the decentralized multi-agent bandit literature (Cesa-Bianchi et al, 2019a;.…”
Section: Local Communicationmentioning
confidence: 99%
“…Finally, the reader may wonder what kind of results could be achieved if the agents are activated adversarially rather than stochastically. Cesa-Bianchi et al [2019a] showed that in this setting no learning can occur, not even in with full-information feedback.…”
Section: Related Work and Further Applicationsmentioning
confidence: 94%
“…In our multi-agent setting, the end goal is to control the total network regret (1). This objective was already studied by Cesa-Bianchi et al [2019a] in the full-information case. A similar line of work was pursued by Cesa-Bianchi et al [2019b], where the authors consider networks of learning agents that cooperate to solve the same nonstochastic bandit problem.…”
Section: Related Work and Further Applicationsmentioning
confidence: 99%